2017
DOI: 10.1016/j.addbeh.2016.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence between adolescent and informant reports of substance use: Findings from the Philadelphia Neurodevelopmental Cohort

Abstract: Inclusion of collateral informant reports is common in adolescent psychopathology research and clinical assessment, yet few studies have examined agreement on ratings of adolescent substance use or factors that may be associated with reporter agreement. The present study aimed to extend prior work on the correspondence between adolescent and informant reports of adolescent substance use with data from a large (n=5,214), diverse, community-based sample of youth aged 11–17 (mean age=14.53, SD=1.98; 52% female). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Our measure of alcohol use was based on a single self-report item; although self-reported measures of alcohol consumption have been shown to be valid in adolescents (Donovan, 2004; Smith et al, 1995), and particularly so with web-based data collection (Turner et al, 1998), there is still potential for self-report bias. While other assessment methods (e.g., parent report) would add to the richness of our data, other investigations have shown that underestimation of child alcohol use is common and severe (Jones et al, 2017), and it’s unclear how such discrepancies would be resolved in this study. Also related to measurement, although we distinguished between norms held by general peers versus close friends, the scale assessing close friends’ norms included both descriptive and injunctive norms, where the scale assessing peer norms assessed only descriptive norms.…”
Section: Discussionmentioning
confidence: 92%
“…Our measure of alcohol use was based on a single self-report item; although self-reported measures of alcohol consumption have been shown to be valid in adolescents (Donovan, 2004; Smith et al, 1995), and particularly so with web-based data collection (Turner et al, 1998), there is still potential for self-report bias. While other assessment methods (e.g., parent report) would add to the richness of our data, other investigations have shown that underestimation of child alcohol use is common and severe (Jones et al, 2017), and it’s unclear how such discrepancies would be resolved in this study. Also related to measurement, although we distinguished between norms held by general peers versus close friends, the scale assessing close friends’ norms included both descriptive and injunctive norms, where the scale assessing peer norms assessed only descriptive norms.…”
Section: Discussionmentioning
confidence: 92%
“…However, given recent evidence for the validity of self-report data (Chan, 2009), our extensive focus on protecting confidentiality as part of our procedures, and the fact that rates of AOD use in the sample match national norms (Johnston et al, 2013), we do not believe this issue affected our results. Moreover, research has suggested that parents report lower estimates of participation in risky behavior than their children, including sexual activity, AOD use, and antisocial behaviors (Jones et al, 2017; Stanton et al, 2000; Yang et al, 2006). Therefore, we believe that basing our analyses on youth-reported data yields a more accurate estimate of the true prevalence of these behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies show inconsistent findings with regard to reporting accuracy across informants in reporting substance use. Some research has found kappas as low as .01-.48 between collateral report and self-report (Jones et al, 2017), which hover in the range of typical parent-youth agreement about behavioral problems in general (De Los Reyes et al, 2015). Some interpret this as suggesting either one or the other perspective may not be accurate, and others advocate treating endorsement by either party as indicating a problem (De Los Reyes et al, 2015).…”
Section: Achenbach System Of Empirically Basedmentioning
confidence: 99%